Visible sign : an introduction to semiotics in the visual - Crow David, 1962- (Lausanne : AVA Academia, 2010)
'Visible Signs: An Introduction to Semiotics' (2nd Edition) is an update to the popular first edition of the same name, in which David Crow introduces design students to the fundamentals of semiotics. Basic semiotic theories are taught in most art schools as part of a contextual studies programme, but many students find it difficult to understand how these ideas might impact on their own practice.'Visible Signs' tackles this problem by explaining semiotic terms and theories in relation to visual communication, with illustrative examples taken from contemporary art and design. Concepts such as signs and signifiers, and language and speech are all explored within the framework of graphic design and fine art. The 2nd Edition features new and revised content from the author, and includes 200 visuals created to illustrate the ideas discussed within the book.' -- Publisher description.
Previous ed.: 2003
'Required reading range course reader' -- from t.p.
Includes bibliographical references and index.
Keywords: Semiotics; Semiotics and art; Visual communication